Features Of the Formation of a System of Social and Value Orientations of Women (Zien Journal of Social Sciences and Humanities, 2022)
In the article, the author touches on the issues of social and value targeting women. With the expansion of the role of women in social production, there is a process of qualitative change on the part of all strata of society towards the female factor. This new social state of women is facilitated by the purposeful policy of our young state to empower women in the public life of the country. That women's rights are primarily guaranteed by the Constitution of the Republic of Uzbekistan